Understanding the power transformer component failures for health index-based maintenance planning in electric utilities. (February 2019) - Murugan, Raji; Ramasamy, Raju
Abstract: This article presents an analysis of 343 distribution and power transformer component failures in the voltage range of 33 kV–400 kV over an operational period of 11 years from Tamil Nadu Electric Utility (TNEU), India. Two methods were employed in this study. Initially, failure data were analyzed using statistical analysis and grouped into four major failure level which includes electrical, thermal, mechanical and insulation degradation. Further, causes of failure were also identified through maintenance records, direct observations in repair yard and expert consultations. Subsequently, a Health Index (HI) approach to transformer maintenance has been proposed for implementation. By adopting this approach, a case study was presented where a health index was calculated for seven power transformers. The results of HI were used for maintenance decisions such as: should the transformer continue in service, be repaired, be refurbished, or be replaced. This study provides a practical guidance to maintenance personnel for early fault diagnosis that prevents unexpected failure of in-service power transformers and reduce maintenance cost in electric utilities. Highlights: Utility power transformer component failures data are analyzed. Major failure modes are identified, namely electrical, thermal, mechanical and oil-paper degradation. Significant causes of power transformer component failures are also identified. Health Index (HI) approach to transformer maintenance has been proposed for preventing early failures.